Effect of Tritium-Induced Damage on Plastic Targets from High-Density DT Permeation. (3rd April 2018) - Wittman, M. D.; Bonino, M. J.; Edgell, D. H.; Fella, C.; Harding, D. R.; Sanchez, J.
Abstract: Direct-drive inertial fusion experiments conducted at the Laboratory for Laser Energetics implode 860-μm-diameter, 8-μm-thick glow-discharge polymer (GDP) capsules that have a solid, uniform, 60- to 80-μm-thick layer of an equimolar mixture of deuterium and tritium (DT) on their interior. The DT is permeated through the capsule's wall up to pressures of 1000 atm in small pressure steps to prevent buckling; this occurs over many hours. The capsule is then cooled, the DT is solidified, and the uniform layer is formed using thermal gradients produced by heat deposited from beta decay of the tritium. Thermal contraction of the capsule from cooling is expected to be ~1% of the diameter. Capsules permeated with DT do not exhibit this contraction and retain their room-temperature diameter after cooling. Sources of error in the imaging system were explored, and a systematic 3 μm over measurement of the diameter was revealed and corrected. However, both GDP capsules permeated with only deuterium and polystyrene capsules permeated with DT do exhibit thermal contraction. The highly cross-linked GDP shell is under compressive stress after fabrication and experiences bond breakage when exposed to high-density DT during permeation. It is speculated that some of this compressive stress is relieved during bond cleavage and the capsule's wall swells, which counteracts contraction during cooling. In addition, mass spectrometry of the DT gas in the permeation system has revealed the presence of hydrocarbons and other carbon-containing species that increase with time, confirming the radio-degradation of the polymer.